2020
DOI: 10.1002/jcla.23375
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T‐cell senescence and skewed lymphocyte subsets in young Dyskeratosis Congenita patients with PARN and DKC1 mutations

Abstract: Background Dyskeratosis congenita (DC) is a syndrome resulting from defective telomere maintenance. Immunodeficiency associated with DC can cause significant morbidity and lead to premature mortality, but the immunological characteristics and molecular hallmark of DC patients, especially young patients, have not been described in detail. Methods We summarize the clinical data of two juvenile patients with DC. Gene mutations were identified by whole‐exome and direct sequencing. Swiss‐PdbViewer was used to predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Similar to our results, skewed lymphocyte subsets, cytotoxic T‐cell senescence and strong CD23 expression on B cells were reported in patients with DC caused by mutations in PARN and DKC1 genes 16 . Also, immunoglobulin level abnormalities were reported in several published cases which might be unique to DC in comparison to patients with acquired BMFSs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to our results, skewed lymphocyte subsets, cytotoxic T‐cell senescence and strong CD23 expression on B cells were reported in patients with DC caused by mutations in PARN and DKC1 genes 16 . Also, immunoglobulin level abnormalities were reported in several published cases which might be unique to DC in comparison to patients with acquired BMFSs.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our results, skewed lymphocyte subsets, cytotoxic T-cell senescence and strong CD23 expression on B cells were reported in patients with DC caused by mutations in PARN and DKC1 genes. 16 Also, immunoglobulin level abnormalities were reported in several published cases Standing height using a portable stadiometer was measured to the nearest millimetre and weight was measured using an electronic scale to the nearest 100 g. Body mass index (BMI) was computed by dividing weight in kilograms by height in metre squares. Subsequently, the height, weight and BMI were converted to Z scores using Egyptian/WHO normative data.…”
Section: Discussionmentioning
confidence: 99%
“…We also found 13 variants of DKC1 in Asia with 100% male ( 7 , 9 , 13 , 20 , 23 , 28 , 32 , 35 , 36 , 40 ), 52 variants in non-Asia with 84.8% male ( 1 , 8 , 10 14 , 16 19 , 21 , 24 26 , 29 , 31 , 33 , 34 , 37 , 38 , 41 , 42 , 44 , 45 ), and 10 variants with unknown nationality ( 3 , 4 , 30 ). Asians develop DC at a younger age than non-Asians, between 4.3 and 46 years old ( 1 , 7 – 12 , 14 , 16 24 , 26 , 28 , 29 , 31 35 , 38 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Through whole exome and sequencing of patients with congenital dyskeratosis (DC), the study found that there were compound heterozygous mutations (c.204 g > T and c.178-245del) in PARN. At the same time, B cells and NK blood cells were also detected to be reduced, the ratio of CD4:CD8 was inverted, and naive CD4 and CD8 cells were reduced ( Zeng et al, 2020 ). However, in sepsis, lymphocytopenia and T-cell depletion are often found to be immunopathological characteristics ( van der Poll et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%